Livelihood and coping strategy changes along rural-urban continua with an emphasis on natural resources,Livelihood and coping strategies changes along rural-urban continua with an emphasis on natural resources - Evans, Michelle Leigh (Rhodes University, Faculty of Science, Department of Environmental Science, 2013)
Rapid urbanisation is one of the greatest challenges facing both developed and developing countries. Sub-Saharan Africa has historically been one of the least developed and least urbanised areas of the world. However, urbanisation is now occurring much more rapidly in countries that have lower levels of per capita income. Therefore, in the coming decades, urban population growth is expected to be more widespread in the developing countries of the world. Most research on the role of natural resources focuses on rural communities and little is known about the contribution these resources make along the rural-urban continuum in small and medium sized towns as well as the contribution to total livelihoods. This is because researchers and policy makers have often treated rural and urban areas and their residents as distinct entities that should be studied in isolation. This, however, is not a true reflection of household livelihoods which often include both rural and urban elements. This study therefore analysed the impact of urbanisation on livelihoods along a rural-urban continuum with an emphasis on natural resources in South Africa. The main characteristics as well as the livelihood portfolios of respondent households were investigated. Secondly, the coping strategies used by households along the rural-urban continuum were explored, and disaggregated according to the gender of the household head. Data were collected along the rural-urban continuum of two small towns, namely Queenstown, located in the Eastern Cape province and Phalaborwa, located in the Limpopo Province of South Africa. Sampling covered the town, peri-urban areas, townships and adjacent rural households. A standardised survey instrument was used to capture household details and livelihood activities and a total of 272 interviews were conducted. The rural areas near both towns were poorer than the township and urban areas with regards to assets, access to employment and annual household income across all cash and non-cash income streams. The engagement in land-based activities increased towards the rural areas. The use of natural resources, as well as the number of resources collected, increased along the continuum towards the rural areas, with 12.0% to 49.0% of urban households, 30.0% to 88.0% of township households and between 80.0% and 100.0% of rural households engaging in the use and collection of natural resources. While natural resource use and collection was lowest in the urban areas, a significant amount of resources were still collected by urban households. Income portfolios for all households were calculated to determine the direct-use value of wild natural capital to livelihoods as well as the contribution made from land (arable and livestock farming), welfare grants and employment. Employment, barring one exception in the rural areas of Phalaborwa, was the largest contributor in terms of mean annual income along the continuum in both towns, followed by grants and pensions in the township and rural areas. In Phalaborwa, however, wild natural capital was found to be the largest contributor to local livelihoods, contributing 48.0% of the mean annual income. Household portfolios become more diversified in the poorer, rural areas as well as in households headed by females. The main shocks reported along the continuum in both Queenstown and Phalaborwa were death in the family, followed by a loss of employment, which was concentrated in male-headed households. Coping strategies resulting in the attainment of cash income fast, such as borrowing money from friends/relatives and cashing in retirements savings were favoured over longer term strategies such as finding local wage employment. Female-headed households were found to rely significantly on social groups or clubs as a coping strategy, highlighting the importance of social capital and social relations in female-headed households
Keywords: Natural resources -- South Africa -- Queenstown; Natural resources -- South Africa -- Phalaborwa; Rural-urban divide -- South Africa -- Queenstown; Rural-urban divide -- South Africa -- Phalaborwa; Income -- South Africa -- Queenstown; Income -- South Africa -- Phalaborwa; Women heads of households -- South Africa -- Queenstown; Women heads of households -- South Africa -- Phalaborwa; Adjustment (Psychology)